PENINGKATAN HASIL BELAJAR MATERI BANGUN RUANG DENGAN MEDIA BENDA KONKRET PAPERCRAFT KELAS II - Mariyana, Freni; Anisa, Lutfi Nur; Rakhmawati*, Yeni (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2022)
The low student learning outcomes due to the lack of motivation and interest in student learning in mathematics is the background of this research. To overcome these problems, the learning media used Papercraft concrete objects. The purpose of this research is to improve student learning outcomes using concrete object media Papercraft math subject on geometric material in class II students. This research was conducted in November 2022 in class II of SD 2 Jurang Gebog Kudus for the 2022/2023 academic year, with a total of 11 students. The research was carried out in 2 cycles with each cycle consisting of: a. Planning; b. Action; c. Observation; and D. Reflection. In cycle 1, the learning outcomes were 6 students or 54.5% who succeeded in obtaining a score above the specified Minimum Completeness Criteria (KKM), namely 67. Meanwhile, 5 students or 45.5% were below the KKM. The results of student mastery learning increased in cycle 2, namely 10 students or 91% who succeeded in obtaining a score above the KKM and 1 student or 9% below the KKM. Based on these facts, it can be concluded that the use of papercraft media can improve the understanding and skills of mathematics subjects about building space for class II SD 2 Jurang District, Gebog District, Kudus Regency.